2018
DOI: 10.1007/s40843-017-9184-1
|View full text |Cite
|
Sign up to set email alerts
|

Room-temperature sintered metal-organic framework nanocrystals: A new type of optical ceramics

Abstract: Ceramic is a rigid material consisting of an infinite threedimensional network of sintered non-oriented inorganic, non-metallic crystalline grains, which are generally nontransparent. If the inner light scatter is eliminated, ceramics can become transparent or optical ceramics [1,2]. With great potentials in optical windows, sensors and lasers, optical ceramics have received great attentions since 1950s [1]. As the gain medium of solid-state lasers, optical ceramics can combine the advantages of large size, hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 30 publications
1
11
0
2
Order By: Relevance
“…Optical ceramics is a transparent special ceramic that combines the high stability of single crystals with the large size of glass, fluid, and other amorphous materials, which is a potential carrier for the laser gain medium . Ye et al reported a novel metal‐organic optical ceramic (MOOC, MOOC‐1) consisting of a metal‐organic framework MAF‐4 (also known as ZIF‐8) . By simply reducing the rate of solvent evaporation, MAF‐4 nanocrystals can be fused to form dense ceramic‐like blocks with millimeter size and up to 84% visible light transmission ( Figure a).…”
Section: Host–guest Mof‐based Microlasersmentioning
confidence: 99%
See 1 more Smart Citation
“…Optical ceramics is a transparent special ceramic that combines the high stability of single crystals with the large size of glass, fluid, and other amorphous materials, which is a potential carrier for the laser gain medium . Ye et al reported a novel metal‐organic optical ceramic (MOOC, MOOC‐1) consisting of a metal‐organic framework MAF‐4 (also known as ZIF‐8) . By simply reducing the rate of solvent evaporation, MAF‐4 nanocrystals can be fused to form dense ceramic‐like blocks with millimeter size and up to 84% visible light transmission ( Figure a).…”
Section: Host–guest Mof‐based Microlasersmentioning
confidence: 99%
“…c) The pumping energy density‐ dependent fluorescence of SRh@MOOC‐1. Reproduced with permission . Copyright 2018, Science China Press and Springer‐Verlag GmbH Germany, part of Springer Nature.…”
Section: Host–guest Mof‐based Microlasersmentioning
confidence: 99%
“…Through filtration, the reaction product is collected for further solvent evaporation in order to obtain purified MOF crystals [37,38]. With this method, Ye et al [39] synthesized a new type of ceramic base MOF: the crystal size and the symmetry of the product as well as the calcination temperature need to be strictly controlled in this preparation, and there are few inorganic non-metallic materials that can form optical ceramics. However, using the conventional solution method, the nanocrystals denoted as MAF-4 (sodalite-type zinc dimethyl imidazole known as ZIF-8) was able to produce a dense ceramic-like block.…”
Section: Juc-167mentioning
confidence: 99%
“…Thus, MOFs demonstrate great potential applications in various fields. Owing to the decades' efforts of researchers, thousands of structures of MOFs have been discovered and applied in various fields, such as separation [31][32][33][34][35][36][37][38], adsorption [20,[39][40][41][42], optics [43][44][45][46][47][48][49][50], catalysis [19,[51][52][53][54][55][56], sensors [57][58][59][60][61][62][63], etc. However, most of these studies are based on MOFs powders.…”
Section: Introductionmentioning
confidence: 99%